Applying experimental micro-tool wear measurement techniques to industrial environments. (August 2021) - Alhadeff, Lisa; Marshall, Matthew; Curtis, David; Slatter, Tom
Productivity in micro-milling is hindered by premature fracture of tools and difficulty predicting wear. This work builds upon previous investigations into tool wear mechanisms and coatings for micro-mills.The technology readiness level of this work exceeds previous studies by investigating the micro-mills for practical applications and comparing this data. 0.5 mm micro end mills are tested with different coatings on CuZn38, and wear curves produced both in the case of simple straight slot testing and milling of complex parts representing industrial applications. The results show that curves produced using straight slots can be used to predict the behaviour of tools used to machine industrial parts. Due to interrupted cutting, tools used in straight slot tests reach the end of steady state wear after approximately 12 s of cutting as compared with 170 s in continuous milling. Typical cutting forces seen for the tools are in the order of 2–4 N. Catastrophic failure is seen towards the end of tool life for a TiAlN tool with a cutting force of over 30 N seen. For the first time a comparison has been made between fundamental tool wear studies and tool wear observed when producing test pieces representative to micro-industrial parts. This presents a novel perspective on tool wear and facilitates the integrating of existing micro-milling research into industry